Religion, Welfare and Social Service Provision. Common Ground - Wineburg, Robert (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Religion, Welfare, and Social Service Provision: Common Ground delves deeply into the partnerships forged between religious communities, government agencies and nonprofits to deliver social services to the needy. These pages offer a considered examination of how local faith entities have served those in their midst, and how the provision of those services has been impacted by evolving social policies. This foundational volume brings together the work of more than two dozen leading researchers, each providing long overdue scholarly inquiry into religiously affiliated helping and the many possibilities that it holds for effective cooperation.